Identifikasi dan Upaya Penanggulangan Cacat Konstruksi Bangunan Perumahan Menggunakan Metode Six Sigma - Bowo Prihatno; Wulfram Indri Ervianto; Peter Fortunatus Kaming (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
ABSTRACT: This study aims to identify construction defects in residential buildings of type 50 and smaller in the Special Region of Yogyakarta, examine the efforts of housing developers in overcoming construction defects, as well as the level of suitability and comfort of residential buildings according to consumers. This study adopted Six Sigma method as an instrument to get the value of construction defects. Data collection is done by distributing questionnaires confirmed by interviews, as well as observations to residential buildings. Respondents numbered 14 residential consumers, 8 housing developers. Observations by researcher in 8 housing units. The results showed construction defects as a result of consumer identification was 20.87%, while theresults of the identification of researcher were 25.40%. The efforts to overcome construction defects with the lowest value are: the formal application of a quality management system. The biggest obstacle in developing small types of housing is land prices. The level of feasibility of housing received an answer 50% of respondents said it was feasible, 50% of respondents said it was quite feasible. The level of comfort of residential housing gets the answer 28.6% of respondents said it was comfortable, 57.1% of respondents said it was quite comfortable, and 14.3% of respondents said it was uncomfortable. ABSTRAK: Penelitian ini bertujuan untuk mengidentifikasi besaran cacat konstruksi bangunan perumahan tipe 50 dan lebih kecil di Daerah Istimewa Yogyakarta, mengkaji upaya pengembang perumahan dalam menanggulangi cacat konstruksi, serta tingkat kelayakan dan kenyamanan huni bangunan perumahan menurut konsumen. Penelitian ini mengadopsi metode six sigma sebagai instrumen untuk mendapatkan nilai cacat konstruksi. Pengumpulan data dilakukan dengan menyebarkan kuesioner yang dikonfirmasi dengan wawancara, serta observasi ke bangunan perumahan.Responden berjumlah 14 konsumen perumahan, 8 pengembang perumahan. Observasi dilaksanakandi 8 unit perumahan. Hasil penelitian menunjukkan besaran cacat konstruksi hasil identifikasi konsumen adalah 20,87% sedangkan hasil identifikasi peneliti adalah 25,40%. Upaya penanggulangan cacat konstruksi dengan nilai terendah adalah: penerapan sistem manajemen mutu secara formal. Kendala terbesar dalam pengembangan perumahan tipe kecil adalah harga tanah. Tingkat kelayakan huni perumahan memperoleh jawaban 50% responden menyatakan layak, 50% responden menyatakan cukup layak. Tingkat kenyamanan huni perumahan memperoleh jawaban 28,6% responden menyatakan nyaman, 57,1% responden menyatakan cukup nyaman, dan 14,3% responden menyatakan kurang nyaman.